The relation to question about receiving monogynopaedium: some legal aspects - Bytrun-Boka, Natalia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
This article is devoted research of one of forms of arranging of children deprived of paternal guardianship – receiving family. Legislative acts which regulate the order of adoption of children-orphans are analysed. An author is conduct a doctrine and normative analysis. Certain results and results are shown out